2023
DOI: 10.3390/met13010150
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Differential Scanning Calorimetry Study of Precipitation Hardenable Copper-Based Alloys with Optimized Strength and High Conductivity

Abstract: Copper alloys with chromium, hafnium, and scandium combining enhanced strength as well as high electrical and thermal conductivity are analyzed in depth. The aim is to compare the precipitation process during temperature exposure to meet increasing material requirements. This research focuses on alloying elements having a limited, maximum 1 wt.%, and with temperature decreasing solubility in copper. For the simultaneous enhancement of mechanical strength and conductivity, precipitation hardening is the utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 71 publications
8
0
0
Order By: Relevance
“…In addition, the curves show the peak of the second exothermic reaction (indicated by the number 1 with arrows), which can be attributed to recrystallization of the microstructure. This investigation agrees with the findings of Dölling et al [31] obtained with a directly comparable experimental setup and raw materials. The obtained peak temperature values related to Cu4Sc precipitation as a function of heating rates are shown in Table 1.…”
Section: Dsc Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, the curves show the peak of the second exothermic reaction (indicated by the number 1 with arrows), which can be attributed to recrystallization of the microstructure. This investigation agrees with the findings of Dölling et al [31] obtained with a directly comparable experimental setup and raw materials. The obtained peak temperature values related to Cu4Sc precipitation as a function of heating rates are shown in Table 1.…”
Section: Dsc Analysissupporting
confidence: 93%
“…The DSC scans at different heating rates (10, 15, 20, and 40 K/min) for the nondeformed CuSc0.4 specimen (Figure 2a) all show an exothermic peak (Exo) between 760 K and 950 K. A closely related study by Dölling et al [31] showed highly comparable curves for a non-deformed CuSc0.3 alloy at a 10 K/min heating rate with a peak temperature of 842.1 K. Furthermore, there was no recrystallization detected for non-formed Cu-Sc specimens, resulting in only a single peak indicating the precipitation reaction.…”
Section: Dsc Analysissupporting
confidence: 68%
“…The curves also show peaks of the second exothermic reaction (arrows 1), which can be attributed to a recrystallization of the microstructure. This investigation agrees with the findings of Dölling et al [31] with a directly comparable experimental setup and the chosen raw material. The obtained peak temperature values related to Cu4Sc precipitation as a function of heating rates are shown in Table 1.…”
Section: Dsc Analysissupporting
confidence: 92%
“…The fine lamellar structures (dark grey) are homogeneously distributed within the copper matrix (light grey). The characteristics of the Cu4Sc precipitates are comparable to those of Dölling et al [31], which were analyzed at the same heating rate but slightly lower final temperature (600 °C). Energy Dispersive X-ray spectroscopy (EDX) showed that these structures are directly associated with an increased scandium content.…”
Section: Microstructure Analysissupporting
confidence: 74%
See 1 more Smart Citation